Biomimetic study on honeycomb energy absorption structure based on straw micro-porous structure - Zhang, Yangyang; Li, Shaopeng; Zhu, Jiawen; Zou, Meng; Xu, Shucai; Song, Jiafeng (Frontiers in Materials, 2025)
In this paper, sorghum and reed, light stem structures in nature, are selected as biomimetic prototypes. According to their mechanical stability characteristics-the porous structure at the node feature and the porous feature in the outer skin, the biomimetic optimization design, simulation and experimental research on the traditional hexagonal structure and hexagonal honeycomb structure are carried out. The results show that the performance of combined honeycomb structure is the best, and its specific energy absorption is 22.82% higher than that of the traditional hexagonal structure.